2015
DOI: 10.47197/retos.v0i19.34636
|View full text |Cite
|
Sign up to set email alerts
|

La velocidad y la precisión en el lanzamiento en jóvenes jugadores de balonmano en función de la concentración de la práctica (The speed and accuracy in the shot in young handball players according to the concentration of practice)

Abstract: El presente trabajo tiene como objetivo analizar los valores de la velocidad y de la precisión en el lanzamiento de siete metros en balonmano con jóvenes jugadores en función de la distribución de la práctica. En este estudio han participado dos grupos de diez jugadores de balonmano de categoría infantil (12,5 años, SD=0,9). Cada uno de estos dos grupos ha sido sometido a dos condiciones de práctica diferente (práctica concentrada y distribuida), en tres series de lanzamientos. Los resultados han mostrado que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Currently continues the dispute and the conflicting results about both practice schedules on discrete skills. A study of handball players (García-Herrero et al, 2011) revealed that massed practice led to less accuracy and velocity in throws as the amount of practice increased. Others researches also revealed a decline in the learning performance of a coincident timing task when massed practice was used (Leite et al, 2013).…”
Section: Preprintsmentioning
confidence: 99%
“…Currently continues the dispute and the conflicting results about both practice schedules on discrete skills. A study of handball players (García-Herrero et al, 2011) revealed that massed practice led to less accuracy and velocity in throws as the amount of practice increased. Others researches also revealed a decline in the learning performance of a coincident timing task when massed practice was used (Leite et al, 2013).…”
Section: Preprintsmentioning
confidence: 99%
“…Under the perspective of complex dynamic systems, variable practice, in which the execution conditions are modified, could affect learning, especially in open tasks (Davids et al, 2003;Douvis, 2005), as in the case of tennis strokes (Crespo, 2009;Sahan et al, 2018). In this sense, the variability induced could be a stimulus that leads to improvements in performance (Bernacki et al, 2015;Dhawale et al, 2017;García-Herrero et al, 2011;Menayo et al, 2010). However, for inexperienced athletes, the benefits of variability when practicing are not strongly evident in throwing and hitting skills (Alfonso-Asencio and Menayo, 2019;Hernández-Davó et al, 2014a,b;Taheri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Edición Web: 1988-2041 et al, 2016;Saavedra et al, 2018;Taylor, Wright, Dischiavi, Townsend, & Marmon, 2017). Además de las habilidades técnico-tácticas, se ha argumentado que uno de los factores clave en el rendimiento es la velocidad de lanzamiento del balón (Gorostiaga, Granados, Ibanez, & Izquierdo, 2005) y el nivel de concentración (García, Moreno, Reina, & Menayo, 2015). A diferencia de otros deportes, como el fútbol y el rugby, la cantidad de lanzamientos a portería que se producen durante un en-Fecha recepción: 13-08-20.…”
Section: Introductionunclassified